PENGEMBANGAN E-MODUL BERBASIS RESEARCH BASED LEARNING BERBANTUKAN 3D PAGE FLIP PRO PADA PELAJARAN IPAS UNTUK MENDUKUNG MERDEKA BELAJAR DI KELAS IV SEKOLAH DASAR - Sri Yunimar Ningsih; Estuhono Estuhono; Jamila Turrohmah (Jurnal Tunas Pendidikan, 2023)
ABSTRACK Jamila.Turrohmah, 2023. Development of research based learning (RBL) e-modules with the help of 3d page flip pro in science lessons to support independent learning for grade IV elementary schools. Dharmasraya : Elementary School Teacher Education Study Program. Dharmas University Indonesia. This research is based on the low learning enthusiasm of students due to the lack of teaching materials used in schools. The teaching materials that have been developed are e-modules based on research based learning models that reflect 3d page flip pro aplications in grade iv elementary school science lessons. This type of development research uses the ADDIE model which consist of the design analysis, desgin, development, implementation, and evaluation stages. The analysis phase includes needs analysis. The design stage is the design of the e-module and the validity sheet. The development stage, namely product development to the validator. The evaluation stage is to improve all suggestions from validators and practitioners for product feasibility. The results of the e-module validation research conducted by three experts obtained an average value of 92% by category â€œhighly validâ€. The results of the practicality value obtained from educators and students have an average value of 91,2% in the â€œ very practicalâ€category. The results of the effectiveness value in the value in the form of questions filled out by students obtained a value of 91,70% in the â€œvery effectiveâ€ category. This study produced an e-module with very effective, very practical, and veru effective criteria. Keywords : Natural Science and Social Science, Research Based Learning, 3D Page Flip Pro.